2020
DOI: 10.1021/acs.iecr.0c01663
|View full text |Cite
|
Sign up to set email alerts
|

Decoration of Graphene Quantum Dots on TiO2 Nanostructures: Photosensitizer and Cocatalyst Role for Enhanced Hydrogen Generation

Abstract: Production of H2 fuel from photocatalytic splitting of water is one of the most demanding research studies in terms of sustainable development in the energy sector. In our quest to find an effective photocatalyst for H2 production, we prepared graphene quantum dots/TiO2-based nanocomposites using a simple hydrothermal method and studied the effect of varying morphologies of TiO2 on photocatalytic H2 production. The crystal structure, morphology, surface, and optical properties were thoroughly studied by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…[34][35][36] The derived GQDs show unique optical properties due to disordered structures and defect sites which has been explained in detail in our previous study. [37] In this study, we have extended the application of the efficient photocatalyst composed of varied percentage of "metal free" GQDs decorated TiO 2 , previously reported by our research group, [23] as a means of employing a sustainable approach for the application of photocatalytic degradation of industrial pollutants, [36][37] in this case, MB under visible-light. Amidst different compositions GQDs incorporated TiO 2 nanostructures, the photocatalytic system comprising of TiO 2 nanotubes and 2 wt% GQDs were found to display a degradation efficiency of 96.7 % towards MB under visible light irradiation of 120 min.…”
Section: Introductionmentioning
confidence: 79%
“…[34][35][36] The derived GQDs show unique optical properties due to disordered structures and defect sites which has been explained in detail in our previous study. [37] In this study, we have extended the application of the efficient photocatalyst composed of varied percentage of "metal free" GQDs decorated TiO 2 , previously reported by our research group, [23] as a means of employing a sustainable approach for the application of photocatalytic degradation of industrial pollutants, [36][37] in this case, MB under visible-light. Amidst different compositions GQDs incorporated TiO 2 nanostructures, the photocatalytic system comprising of TiO 2 nanotubes and 2 wt% GQDs were found to display a degradation efficiency of 96.7 % towards MB under visible light irradiation of 120 min.…”
Section: Introductionmentioning
confidence: 79%
“…[145][146][147] In fact, the GQDs composites are more efficient and popular photocatalysts in which the GQDs serves as the visible light photosensitizers. For example, Raghavan et al [148] reported the synthesis of GQDs/ TiO 2 (CTNT) and GQDs/P25 (GTNP) composite photocatalysts via the hydrothermal route and investigated the effect of TiO 2 morphology varying on the performance of the photocatalyst for H 2 evolution. The TEM and HRTEM micrographs of CTNP composite are revealed in Figure 6A,B.…”
Section: Carbon Quantum Dots (Cqds) Compositesmentioning
confidence: 99%
“…According to the suggested mechanism Reproduced with permission. [148] Copyright 2020, The American Chemical Society.…”
Section: Carbon Quantum Dots (Cqds) Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…CDs/KNbO 3 photocatalytic system was reported by Qu et al., [33] wherein CDs played the role of a co‐catalyst and the composite system exhibited excellent photocatalytic activity with concomitant evolution of hydrogen. In our earlier research, we also reported on graphene quantum dots (GQDs) based TiO 2 nanocomposites for photocatalytic production of hydrogen and discovered that GQD incorporation led to a smaller band gap and improved hydrogen evolution in comparison to that of the commercial, P‐25 TiO 2 nanoparticles [34] . Munevver tuna genc et al., reported CQDs/TiO 2 nanocomposite as photocatalysts for hydrogen production activity under visible light (>420 nm) wherein CQDs were derived from a green biomass source ‘‘Gingko Biloba‘‘.…”
Section: Introductionmentioning
confidence: 99%